Dams vs drinking water - "Jain,L. C" (Pune, 2001)
This book contains following topics: Introduction; The Ideology of the Majority Judgement and its knowledge base; "Dam is the only solution" Majority Judgement; How was the Availability of Narmada Waters Determined? Legal and technical facts the Majority Judgement; Holding the height of the Dam-by inadvertence?; Rehabilitation a sensitive task; The Petition and the Petitioner how treated?
Keywords: Drinking water